2021
DOI: 10.1002/eco.2350
|View full text |Cite
|
Sign up to set email alerts
|

Effects of animal grazing on vegetation biomass and soil moisture on a typical steppe in Inner Mongolia, China

Abstract: Grasslands play a very important role in the water and carbon cycle of arid and semi‐arid areas, where they are the main type of steppe globally. With this said, research into grassland ecological processes mostly consists of single‐factor controlled experiments such as precipitation, temperature or grazing, and few studies have investigated the effects of synergistic interactions between multiple factors on grassland hydrological, soil and vegetation processes. In this study, we set up a prohibited grazing ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 71 publications
(80 reference statements)
0
13
0
Order By: Relevance
“…All finally depleted the soil water content ( Hao and He, 2019 ; Tang et al, 2020 ). The returns of ACa and AMg in form of dung and urine ( Saunders, 2012 ) and accelerated soil weathering by grazing ( Lin et al, 2021 ) could elevate the availability of calcium and magnesium, which, in turn, are conducive to improving soil pH ( Figure 1C ). Decreases in plant biomass and coverage ( Wang and Tang, 2019 ; Lin et al, 2021 ) and removal of aboveground biomass by buffalo eating and treading, and root biomass ( Wade et al, 2022 ) due to the depletion of soil water content, and increased bulk density ( Lin et al, 2021 ) and soil hardness ( Figure 1A ), generally reduced the C inputs, which, in turn, commonly reduced the bioavailable soil C ( Ravhuhali and Moyo, 2021 ), aggravated C limitation ( Goenster-Jordan et al, 2021 ) as indicated by the increased investment in C-capturing enzyme (ßGC, Figure 1H ), which can hydrolyze sugars and release labile C. The vector angle under ungrazed was <45, indicating that the soil microbial communities were limited by N; the vector angle under grazed crossed with 45, indicating that the soil microbial communities were under N and P co-limitation.…”
Section: Discussionmentioning
confidence: 99%
“…All finally depleted the soil water content ( Hao and He, 2019 ; Tang et al, 2020 ). The returns of ACa and AMg in form of dung and urine ( Saunders, 2012 ) and accelerated soil weathering by grazing ( Lin et al, 2021 ) could elevate the availability of calcium and magnesium, which, in turn, are conducive to improving soil pH ( Figure 1C ). Decreases in plant biomass and coverage ( Wang and Tang, 2019 ; Lin et al, 2021 ) and removal of aboveground biomass by buffalo eating and treading, and root biomass ( Wade et al, 2022 ) due to the depletion of soil water content, and increased bulk density ( Lin et al, 2021 ) and soil hardness ( Figure 1A ), generally reduced the C inputs, which, in turn, commonly reduced the bioavailable soil C ( Ravhuhali and Moyo, 2021 ), aggravated C limitation ( Goenster-Jordan et al, 2021 ) as indicated by the increased investment in C-capturing enzyme (ßGC, Figure 1H ), which can hydrolyze sugars and release labile C. The vector angle under ungrazed was <45, indicating that the soil microbial communities were limited by N; the vector angle under grazed crossed with 45, indicating that the soil microbial communities were under N and P co-limitation.…”
Section: Discussionmentioning
confidence: 99%
“…This is most likely due to prohibition of grazing and enclosure implemented in grassland due to ERPs (Wu et al 2013. Prior research has already found that light grazing and enclosure would alter the composition of vegetation species, improve grassland productivity and reduce soil respiration to promote the carbon sink (Deng et al 2017, Lin et al 2021. Another important cause is rising CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Grasslands are of great global economic and ecological importance, covering approximately 40% of the earth's surface (Lin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Grasslands are of great global economic and ecological importance, covering approximately 40% of the earth's surface (Lin et al, 2022). Furthermore, grasslands are the largest terrestrial ecosystem type in China and play a critical role in the country's national ecological and environmental protection planning (Ren et al, 2011).…”
Section: Introductionmentioning
confidence: 99%